Nutritious Diet, Physical Activity and Mobiles. The Game Changers of ADHD - Fotoglou, Anestis; Moraiti, Ioanna; Diamantis, Apostolis; Stergios, Vasilis; Gavriilidou , Zoe; Drigas, Athanasios (Technium BioChemMed, 2022)
Proper nutrition and physical activity over time are alternative interventions for children with ADHD and are recognized in many European countries. Can be applied as an educational and therapeutic practice both in a school environment and in a therapeutic context adjunct to other forms of therapy. THE planning of these interventions aims, on the one hand, to promote its health by reducing the symptoms of ADHD (hyperactivity, behavioral problems) and on the other hand in the development of social and emotional skills such as socializing, playing, and h self-esteem. The purpose of this paper is to record research data on the implementation of diet and exercise programs in the world through a review of the literature. Specifically, many foods have been studied to help children with ADHD, some others are classified as toxic agents and various approaches to physical activity. The results showed that they do exist dietary interventions and physical activity programs that are applied in many countries with positive results in all aspects of the behavior of children with ADHD. The most common foods that help are those high in omega-3 and zinc and those that pose a risk are those that contain sugar and artificial substances. On the other hand, it was checked that they offer positively to children with ADHD approaches such as aerobic exercise and psychomotor activities. Regarding the participants in the interventions, the samples were students with neurodevelopmental disorders studied. The frequency of its application consumption of the labeled foods must be consumed consistently and daily after examinations such as o control ferritin. An aerobic program with a frequency of twice a week and psychomotor intervention once or twice a week is very helpful. In addition, gadgets are listed in this review for the proper organization and regulation of children to cover the difficulties they have, which is very important.